PENGARUH PENAMBAHAN KARAGENAN TERHADAP KARAKTERISTIK FRUIT LEATHER KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) - Monaria Tondang, Heni; Ekawati, I Gusti Ayu; Sri Wiadnyani, AAI. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 2 (2018): Jurnal ITEPA, 2018)
This study aims to determine of various carrageenan concentrations that affect the characteristics from fruit leather of red dragon fruit peel and find out the exact carrageenan concentration to produce fruit leather of red dragon fruit peel with the best characteristics. The experiment used Completely Randomized Design (RAL) with 5 levels of carrageenan concentration treatment ie 0 ; 0.3% ; 0.6% ; 0.9% ; 1.2% of 100 g of red dragon fruit peel. Each treatment was repeated 3 times to obtain 15 units of experiment. The resulting data is then analyzed using anova, and if there is significant effect of the treatment on the observed parameters, then it will be followed by Duncan test.The results showed that the addition of carrageenan treatment had a significant effect on the water content, crude fiber, tensile strength, color, texture. The best treatment was obtained at the treatment of 1,2% of carrageenan with water content of 10.41%, crude fiber 7.02%, antioxidant capacity 0.74%, total sugar 54.24%, tensile strength 2.19 MPa, Sensory evaluation with scores and hedonic test is color very red and liked, texture is chewy and rather liked, aroma and flavor rather liked, overall acceptance liked.